Azobenzene-Based Gel Coated Fibre Bragg Grating Sensor for Moisture Measurement - Mohammed Moniruzzaman; John Rock (International Journal of Polymer Science)
A fibre Bragg grating sensor is coated with a novel polymer gel in order to investigate its suitability for nondestructive measurement of moisture in materials that can potentially lose their integrity due to moisture ingress. Absorption and desorption of moisture lead to swelling/shrinkage of an azobenzene-based gel, which induces a strain in the Bragg grating resulting in wavelength shifts. The results demonstrated that the amount of wavelength shift is linearly dependent on the amount of water ingress by the gel. The performance of the proposed optical fibre moisture sensor was found to be repeatable with no detectable hysteresis and has the potential to offer a low-cost route for monitoring moisture content.